TIR-domain-containing protein C as modulator of innate immune checkpoints - Heine, Leon; Griffiths, Hannah-Miriam; Hu, Huiyun; Müller, Isabelle; Kuhn, Svetlana; Rudolph, Luca; Rait, Xaver; Waldhuber, Anna; Chen, Ying; Miethke, Thomas (Scientific reports, 2025)
The TIR-domain-containing protein C (TcpC), a virulence factor of the uropathogenic Escherichia coli strain CFT073, binds to crucial components of the toll-like receptor-signaling cascade and the NLRP3 inflammasome thus manipulating these innate immune checkpoints and their immune responses. Here we show that TcpC intensified TLR4-dependent pro-inflammatory cytokine secretion by human epithelial cells upon infection with CFT073. Furthermore, TcpC amplified immune responses of monocytic THP-1 cells and peripheral blood mononuclear cells and monocytes during infection. Interestingly, differentiation of monocytes to M0 macrophages reduced the influence of TcpC on innate immune responses. Similarly, polarization of monocytic THP-1 to M1 macrophages impaired partially the ability of TcpC to modulate cytokine secretion. Induced expression of TcpC revealed that increasing levels of TcpC induction augmented the stimulation of THP-1 cells during infection. In contrast, transfer of TcpC-containing culture supernatants from CFT073 to endotoxin plus ATP-stimulated monocytic THP-1 cells revealed the inhibitory function of TcpC. In summary, we show here that TcpC strengthens cytokine release during infection but dampens it during endotoxin-stimulation.
Artikelversion: 28. November 2025
Gesehen am 15.01.2026